Pengembangan Ekowisata Berbasis Ekonomi Peluang Bisnis di Era Revolusi Industri 4.0 Desa Patuanan Kecamatan Leuwimunding Kabupaten Majalengka - Toto Sukarnoto (IAI Bunga Bangsa Cirebon, 2020)
A strong and sustainable regional economic development is an effective collaboration between the use of existing resources, the community and the government. One of the optimal resource utilization efforts is to develop tourism with the concept of Ecotourism. The industrial revolution 4.0 opens wide opportunities for anyone to advance. Information that is very abundant provides great benefits for the development of science and the economy. People in the era of the industrial revolution 4.0 have a very large dependence on using information technology. Based on the background that has been explained, the problem can be formulated through the question